Information and the 21st century Caribbean: a perspective - Sanatan, Roderick (ACURIL [S.l.], 1993)
Draws attention to the emerging scenario of the Caribbean information infrastructure, systems and services. Identifies some of the approaches to forge national information policy, create social justice and use information technology for a new education. Also looks at culture, intellectual property and information specialization.